An action research approach to practice, service and legislative change - Sullivan, E.; Hegney, Desley; Francis, K. (RCN Publishing Company, 2013)
Aims: To describe the action research approach taken to engage a multidisciplinary group of health professionals and managers from five rural health services with government officers in redesigning their emergency care services and informing legislative change. Background: The diminishing size of the medical workforce across rural Victoria in Australia captured the Victorian state government’s attention when this threatened the sustainability of emergency care services in rural and remote hospitals in 2006. The government funded the collaborative practice model pilot between 2006 and 2008 to develop and test an alternative model of emergency care service in which nurses practised at a more advanced and autonomous level. Data sources: Data were sourced from a combination of interviews, focus groups and patient records. Review methods: Qualitative data were analysed using convergent interview and thematic analysis. Quantitative data were analysed using frequencies and cross tabulations. Discussion: The three critical success factors owing to action research are presented. It provided a politically safe approach to service, policy and legislative change, ensured collaboration permeated the endeavour and helped to shift the focus from a technical to an emancipatory approach to action research. Conclusion: Action research was key to the success achieved by the participants in changing clinical practice, service delivery and the Victorian Drugs Poisons and Controlled Substances Act (1981) to authorise registered nurses to supply medicines. Implications for practice: This paper offers an approach that nurses in practice, management and government can take to drive changes at practice, service and legislative levels in advanced nursing practice.